Do Firm Size, Stakeholder Environment, and Internal Environmental Management Influence Small Medium Sized Accounting Firms to Adopt Computerised Accounting Systems? - Biyela, Malusi Gabriel; Muhammad, Kamaruzzaman; Marimuthu, Ferina; Zaini, Syeliya Md (Journal of Ecohumanism, 2024)
Background: In the modern business world, many companies rely on information technology, such as computerised accounting systems, to streamline the preparation of these financial statements. Despite the numerous benefits these systems offer, some organisations still choose to prepare their financial statements manually, exposing themselves to risks such as errors, inefficiencies, a lack of scalability, and limited real-time visibility.Aim: This study examines the influence of firm size, stakeholder involvement, and internal environmental management on the decision of small and medium-sized accounting firms (SMAs) in KwaZulu-Natal, South Africa, to adopt computerised accounting systems. The study uses agency theory to explain the dynamics between the SMAs, who act as agents, and their clients, the principals, who rely on their services to prepare financial statements. Setting: SMAs officially registered with the Durban Chamber of Commerce make up the population frame. Therefore, organisation forms the unit of analysis, which consists of the SMAs located in KwaZulu-Natal, South Africa. Method: This study used a questionnaire survey on 200 SMAs in KwaZulu-Natal, South Africa. Results: This study shows all three factors—firm size, stakeholder involvement, and internal environmental management—significantly and positively influence the decision to adopt computerised accounting systems. Stakeholder involvement, in particular, proves to be the most influential predictor. Conclusion: The introduction of these systems ensures the fast and accurate production of financial information, thus meeting the needs of all stakeholders. Contribution: This study contributes to the existing literature on the factors driving the adoption of computerised accounting systems, with particular focus on the context of KwaZulu-Natal, South Africa.